Long‐term safety and efficacy of a fixed‐combination halobetasol propionate 0.01%/tazarotene 0.045% lotion in moderate‐to‐severe plaque psoriasis: phase 3 open‐label study. (7th February 2021) - Lebwohl, M.G.; Stein Gold, L.; Papp, K.; Han, G.; Pariser, D.M.; Lin, T.; Harris, S.; Jacobson, A.
Abstract: Background: The topical corticosteroid halobetasol propionate (HP) and the retinoid tazarotene (TAZ) are effective in psoriasis treatment. To mitigate adverse cutaneous reactions observed with monotherapy, a fixed‐ combination HP 0.01%/TAZ 0.045% lotion has been developed for the treatment of plaque psoriasis in adults. Objectives: To investigate the long‐term safety, efficacy and maintenance of response with HP/TAZ lotion. Methods: This was a 1‐year, multicentre, open‐label study in 555 adults with psoriasis [Investigator's Global Assessment (IGA) score of 3 ('moderate') or 4 ('severe') and body surface area (BSA) of 3–12% at baseline]. HP/TAZ was administered once daily for 8 weeks and then intermittently as needed in 4‐week intervals for up to 1 year based on achievement of treatment success [IGA score of 0 ('clear') or 1 ('almost clear')]. Maximum continuous exposure was 24 weeks. Results: Of 550 participants with postbaseline safety data, 318 (57.8%) achieved treatment success during the study. Of those, 54.4% achieved treatment success within the first 8 weeks; retreatment was not required for >4 weeks in over half (55.3%), and 6.6% did not require any retreatment. Among participants enrolled for the full 52 weeks, 77.5% maintained BSA ≤5% on treatment. There were marked improvements in severity of itching, dryness and burning/stinging over the study course. The most common treatment‐related adverse events were application site reactions of dermatitis, pruritus, pain and irritation. Conclusions: Fixed‐combination HP/TAZ lotion provided maintained efficacy with a favourable tolerability and safety profile, supporting its use for the long‐term treatment and management of moderate‐to‐severe plaque psoriasis.